Knowledge of endoscopic ultrasound-delivered fiducial composition and dimension necessary when planning proton beam radiotherapy - Gleeson, Ferga C.; Tryggestad, Erik J.; Remmes, Nicholas B.; Beltran, Chris J.; Kruse, Jon J.; Haddock, Michael G.; Hallemeier, Christopher L.; Storm, Andrew C.; Levy, Michael J. (Endoscopy International Open, 2018)
Background and study aims Little consideration has been given to selection of endoscopic ultrasound-guided fiducials for proton radiotherapy and the resulting perturbations in the therapy dose and pattern. Our aim was to assess the impact of perturbations caused by six fiducials of different composition and dimensions in a phantom gel model.Materials and methods The phantom was submerged in a water bath and irradiated with a uniform 10 cm × 10 cm field of 119.7 MeV monoenergetic spot scanning protons delivered through a 45 mm range shifter. The proton “Bragg Peak” was evaluated. Results Dose perturbations manifesting as dose reductions up to 30 % were observed. A carbon composite (1 × 5 mm) and gold (0.4 × 10 mm) fiducial with backload potential rather than dedicated EUS pre-loaded gold fiducial needles had the best performance in terms of minimizing the dose perturbation. Conclusions Our data demonstrate that a carbon composite fiducial has a less untoward effect on proton therapy dose distribution than dedicated EUS pre-loaded gold fiducial needles. Such information is important to consider when selecting fiducials specifically for proton therapy.